1996
DOI: 10.1007/pl00014245
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual development of the patients of the German Collaborative Study of children treated for phenylketonuria

Abstract: In a multicentric and interdisciplinary approach the German Collaborative Study of Children Treated for Phenylketonuria (PKU) investigates prospectively the effects of early started strict dietary treatment on the growth and development of 140 patients. The present paper focuses on longitudinal intelligence data from 4, 5 and 9 years of age of 89 patients in relation to the quality of dietary control in comparison to 200 healthy children tested by the same protocol. Cluster analysis of phenylalanine (Phe) leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 28 publications
3
35
0
4
Order By: Relevance
“…534 deficits or abnormalities of cerebral white matter, as described for patients with mild or classic PKU (7)(8)(9)(10)(11)(12)(13)(14). Because of the limited accuracy of measurements, Phe levels should be taken as an approximation but not as absolute limits in every instance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…534 deficits or abnormalities of cerebral white matter, as described for patients with mild or classic PKU (7)(8)(9)(10)(11)(12)(13)(14). Because of the limited accuracy of measurements, Phe levels should be taken as an approximation but not as absolute limits in every instance.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of early and adequate dietary treatment, patients with mild or classic PKU show a mild reduction of IQ (7)(8)(9), abnormalities of cerebral white matter (10,11), and deficits of fine motor performances (12) and sustained and selective attention (13,14), as well as impaired executive functions depending on (pre)frontal lobe functions (15,16). The latter may be the consequence of a central dopamine depletion.…”
mentioning
confidence: 99%
“…Authors from Heidelberg [33] concluded cautiously from their investigations: '... elevated phenylalanine levels ... resulted in a generalized moderate reduction of intelligence' and 'our results support the recommendation of a strict phenylalanine control during the first decade of life'. In another report this group [36] stated, 'Our studies favour the continuation of a strict diet at least during the first 9 years of life.…”
Section: The 1990s: Time For More Subtle Conclusionmentioning
confidence: 79%
“…Il en résulte une accumulation de phénylalanine dans l'organisme, les concentrations plasmatiques pouvant être 20 à 30 fois plus élevées que la normale. Les études réalisées sur les quotients intellectuels des enfants phénylcétonuriques montrent que les enfants traités dans le premier mois de vie et de façon stricte jusqu'à l'âge de 5 ans ont des performances semblables à celles d'enfants de la population générale, mais infé-rieures d'environ 8 points à celles de leurs germains non atteints [2,3]. Donc, malgré l'instauration du traitement, certains troubles persistent, reflétant une toxicité cérébrale précoce.…”
Section: Aline Ghozlan Arnold Munnichunclassified